Central nervous system infection caused by Mycobacterium houstonense: A case report - Wang, LiXia; Wang, FaPing; Yang, Chuan; Luo, FengMing (Frontiers in Neurology, 2022)
Background: Mycobacterium houstonense is a rapidly growing mycobacteria (RGM) that belongs to the unnamed third biovariant complex of the Mycobacterium fortuitum group, which is hardly responsible for human infection. About 76% of infections caused by M.fortuitum group occurred after skin, soft tissue, bone and puncture wounds, and open fractures. So far, only few cases of human infectious disease caused by M. houstonense were reported worldwide. Case presentation: We present a case of a 26-year-old man with central nervous system(CNS) infection caused by M. houstonense. The patient was transferred to our hospital because of headache and muscle strength changes.One month ago, he patient was diagnosed with tuberculous meningitis at other two hospitals and there was no improvement after anti-tuberculous treatment, antibiotics, and anti-viral treatment before arrival at our hospital. Lumbar puncture was performed both in previous hospitals and our hospital. Both cerebrospinal fluid indicated intracranial hypertension. M.houstonense was detected in cerebrospinal fluid by next generation sequencing(NGS) at the previous hospital,meanwhile,the base sequence of 16sRNA was detected. was included in the base sequence on January 6, 2022 , which‘was not identified in our hospital.The patient was discharged from our hospital after receiving the non-tuberculous mycobacterium(NTM) treatment for one month according to the NTM guidelines of China. However, the patient died 20 days after discharge. Conclusion: Since it is difficult to identify M. houstonense,this is the first case of human CNS infection caused by M. houstonense in China. This case may be considered by neurologists and infectious physicians when CNS infection does not respond to conventional treatment, especially in the uncommon type of NTM.It’s worth exploring the reason of the patient got no improvement after the treatment which was effective reported in other infectious type,although these bacteria infects the skin, soft tissue, or bone mostly.We need more researches to complete the diagnosis and treatment of CNS infection caused by M. houstonense.